Production of insulin using recombinant dna technology - Hafizal, Rabiatul Adawiyah; Shamsudin, Siti Hajar; Mohamed, Elizah; Mohd Fauzi, Noor Akhmazillah (Penerbit UTHM, 2022)
Biotechnology is a technology-related branch of biology. It has so many applications in the fields of agriculture, pharmaceutical and human medicine. Pharmaceutical biotechnology nevertheless has its cornerstones in fermentation and bioprocessing, but the paradigm shift created through biotechnology and pharmaceutical research has resulted in an up-to-date concept. The biotechnological revolution has redefined the processes of drug research, development, manufacturing and marketing. Insulin is one of the finest inventions in medical science in the field of biotechnology applications. Human insulin was formulated in the laboratory under in vitro conditions using recombinant DNA technology that is used for the treatment of a variety of diseases and is widely used in the clinical research industry. Human recombinant insulin was one of the first products of biotechnology. It has been developed in response to the need for consistent and sufficient global supply. This paper will discuss the production of human insulin formulations and the place of recombinant DNA technology in society.